The Comparison of the Sunscreen Activity of Ethanol Extracts and Fractions from Robusta Coffee (Coffea canephora) Leaves using UV Spectrophotometer Method - Krisyanella, Krisyanella; Meinisasti, Resva; Muslim, Zamharira; Salasa, Alfrida Monica; Baharyati, Delta (Riset Informasi Kesehatan; Vol 12 No 2 (2023): Riset Informasi Kesehatan, 2023)
Background : The development of sunscreen preparations has led to the use of natural ingredients as active substances. Robusta coffee leaves ( Coffea canephora ) contain alkaloids, flavonoids, saponins, tannins and steroids. From previous research the SPF value of its ethanol extract at 150 ppm was 12,989 (Maximum protection). The sunscreen activity of its fractions need to be determined, to find out which one has the highest potential sunscreen activities Method : Sunscreen activity examination was carried out in vitro using a UV spectrophotometer. The concetntration of each fraction used was 150 ppm. Results : The N-hexane, ethyl acetate and butanol fractions have sunscreen activity with extra protective power, SPF values respectively were 6.006, 7.609, and 8.046. This activities arises from the content of flavonoids, phenolics and tannins. While the remaining water fraction has the lowest protective activity, with SPF value 3.985 and only contain tannin. Compared to Its ethanol extract, the ethanol extract has better sunscreen activit, because at a 150 ppm it has  SPF value 12.989 (Maximum sunscreen activity) Conclusion : the sunscreen activity of this fraction is lower than its  ethanol extract. The ethanol extract of robusta coffee leaves has more potential to be developed into a sunscreen preparation. Keywords: ; Robusta coffee leaves ; Fraction ; SPF Value